ASEAN-Russia Relations - Chufrin, Gennady (Book collections on Project MUSE., 2006)
With the rise of India and China, the rest of Asia is feeling the great impact of socio-economic changes and challenges created by these twin engines of progress and cooperation. The question on the minds of regional analysts is: Where is Russia in the midst of these vast changes? What is its role? How and why is a great power like Russia adopting such a low profile in the region? In what ways can ASEAN engage Russia?Currently, Russia's interaction with ASEAN is limited to dialogue between ...